Protective effects of Nippostrongylus brasiliensis-derived uridine via the apical sodium-dependent bile acid transporter in a mouse model of TNBS-induced inflammatory bowel disease - Yuan, Caiyi; Wang, Qiang; Chen, Yuying; Ding, Xin; Zhang, Qiang; Yao, Jiakai; Zhang, Bei; Dai, Yang; Bai, Hongxia (Frontiers in Immunology, 2025)
IntroductionInflammatory bowel disease (IBD), a chronic immune-mediated gastrointestinal disorder mainly covering Crohn's Disease and Ulcerative Colitis, has an unclear etiology. The exploration of novel intervention strategies remains a key scientific issue that is urgently needed for IBD treatment. The hygiene hypothesis has led researchers to notice that worm infections can regulate the immune system, which might help treat inflammatory diseases. Nippostrongylus brasiliensis (Nb), similar to human hookworms in life cycle and symptoms, is often used in hookworm research. Our previous study also demonstrated that Nb-derived uridine screened from ES could exert anti-inflammatory and anti-atherosclerotic effects.MethodsIn this study, we established the protective and anti-inflammation effect of Nb infection and ES intervention in TNBS-induced IBD model in mice and further validated the efficiency of uridine screened from ES. Moreover, we conducted an RNA sequencing (RNA-Seq) analysis to elucidate the relevant possible functional mechanisms responsible for the protective and anti-inflammation effects of ES or uridine administration.ResultsCurrent results have demonstrated that uridine can exhibit a protective effect on TNBS-induced IBD in mice. Moreover, it was identified that slc10a2 exhibited high expression after uridine intervention. By specific inhibition of the encoding protein (ASBT), its impact on the protective efficacy has been interrupted.DiscussionThe current study has illustrated that uridine is capable of exerting potential therapeutic and anti-inflammatory effects on Inflammatory Bowel Disease (IBD) by modulating slc10a2. These findings could offer a novel therapeutic target for the intervention of IBD.